A zenei megértés alapjai narratológiai megközelítésben - Szécsi, Gábor; Bogányi , Gergely (Kultúratudományi Szemle, 2022)
The foundations of musical understanding in a narratological approach Gábor Szécsi – Gergely Bogányi Narrative thinking has a significant role in the formation of the self and identity. In fact, to such an extent that the self is seen as the product of narrative thinking, a fictional character emerging at the intersection of autobiographical narratives. The aim of this article is to define the conceptual framework of a narratological model that sheds light on the foundations of musical understanding. We try to achieve this goal by synthesizing the narratological theories born in the field of musicology, music psychology and linguistic, linguistic philosophical and narrative psychological theories discussing the facts of linguistic performance in the narratological context. In the spirit of this synthesis, we argue that the process of musical understanding takes place at the intersection of narratives that are essentially arranged on two levels.